Immune regulatory functions of biologically active proteins from edible fungi - Xu, Juan; Xu, Dazhong; Hu, Qiuhui; Ma, Ning; Pei, Fei; Su, Anxiang; Ma, Gaoxing (Frontiers in Immunology, 2023)
The proteins of edible mushrooms have a variety of biological activities. Here, thirteen precious edible mushrooms such as Ophiocordyceps sinensis, Ganoderma lucidum, and Morchella esculenta and nine common edible mushrooms such as Flammulina velutipes, Pleurotus ostreatus, and Pleurotus eryngii, etc., from which their proteins were extracted, their composition analyzed and their immunomodulatory activity assessed. The results showed that all the different edible mushroom crude proteins increased the proliferation and phagocytosis of mouse macrophages, and we found that these edible mushroom proteins affected the secretion of reactive oxygen species and nitric oxide by mouse macrophages. Further studies on cytokines secreted by mouse macrophages showed a significant increase in pro-inflammatory cytokines, suggesting that edible mushroom proteins promote the polarisation of macrophages into classical M1-type macrophages, further demonstrating that edible mushroom proteins enhance immunity. It was also found that the immunomodulatory activity of the precious edible mushroom proteins was significantly higher than that of the common edible mushroom proteins. These results have important implications for the processing and product development of edible mushroom proteins.